Evolution of STBC-based OFDM-IM for wireless vehicular communication - Mata, Tanairat; Boonsrimuang, Pisit (My University, 2026)
This paper studies wireless vehicular communication (VehCom) in intelligent transportation systems using an orthogonal frequency division multiplexing with index modulation (OFDM-IM). In the concept of IM, data is transmitted not only through the modulated symbols but also via the indices of the active subcarriers. In contrast to the original OFDM, OFDM-IM activates only non-zero subcarriers, increasing energy efficiency. However, the pilot-assisted channel estimation (CE) method is a significant challenge in OFDM-IM, where the desired pilot subcarrier interval is related to the OFDM-IM subblock length. This paper proposes a walsh-scattered pilot-assisted CE for OFDM-IM VehCom. The optimum walsh-scattered pilot assignment is proposed to improve the transmission efficiency. Furthermore, a space-time block code with a high transmit diversity gain is employed for OFDM-IM VehCom to enhance VehCom's signal quality. The results show that the proposed method performs higher CE accuracy and better bit-error rate with significant spectral and energy efficiencies than conventional methods.
Keywords: index modulation; intelligent transportation systems; pilot-assisted channel estimation; space-time block code; wireless vehicular communication